Practice of breastfeeding in quilombola communities in the light of transcultural theory - Lucas Amaral Martins; Rafaele Marques de Oliveira; Climene Laura de Camargo; Aline Cristiane de Sousa Azevedo Aguiar; Deisy Vital dos Santos; Maria Carolina Ortiz Whitaker; Jamile Moreira Machado de Souza (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to identify factors that interfere with the practice of exclusive breastfeeding in quilombola communities. Methods: qualitative research based on the Transcultural Theory proposed by Madeleine Leininger, performed with quilombola mothers. For data collection, we used the semi-structured interview, conducted from June 2018 to January 2019. Content analysis was guided by the interactive model of Miles and Huberman. Results: it was revealed that intergenerational cultural myths and customs interfere with breastfeeding practice, and identified the influence of professional nurses on best breastfeeding practices. Final Considerations: cultural and intergenerational factors favor early weaning and expose the child to illness.